Chronicle of a digital entrepreneurship in the middle of a sanitary crisis: An anthropologist at the company - Mele Arellano, Graziela (2021)
The COVID-19 crisis has generated consequences in our social life and brought out problems especially in the economic aspect. The changes in the global economy were occurring one after another. The markets became more unpredictable, economic models were restructured and companies reinvented themselves. Small businesses with short-term growth were increasingly common to find; and in a certain number of cases, entrepreneurs have shown us that getting out of the status quo is necessary to find “success.” Entrepreneurship today is the protagonist of a boom that is worth documenting. Business Anthropology has much to record, analyze and apply in the near future about entrepreneurship and rapidly growing companies such as startups. This text is a field chronicle based on the anthropological work within a small startup during the period of March to August, 2020. It is based on the first work experience I had and which, coincidentally, was carried out in parallel to a global health crisis. The general objective of the text is to tell the experiences of the work from my anthropological perspective within a company. The chronicle narrated below collects fragments of interviews, reflections and analysis of the positioning of the company “Mamá al rescate.”